Ingestive behavior of hoggets given different types of supplement on ryegrass pasture - Sheila Cristina Bosco Stivanin; Marta Gomes da Rocha; Luciana Pötter; Viviane da Silva Hampel; Renata Aqel de Oliveira; Tuani Lopes Bergoli (Acta Scientiarum. Animal Sciences, 2014)
The ingestive behavior of hoggets was assessed under intermittent grazing method with three days of paddock occupation. These animals remained exclusively on Italian ryegrass (Lolium multiflorum Lam) pasture or on ryegrass pasture and receiving 1.2% of DM in relation to body weight of rice paddy, corn grain or whole rice bran as a supplement during the vegetative, pre-flowering and flowering phenological stages of ryegrass. The experimental design was a randomized split-split plots wherein the types of supplement were considered as main plot, phenological stages as subplot and the days of occupation as sub-subplots. The hoggets grazed for a longer time when kept exclusively on ryegrass pasture. The hoggets grazed for less time in the vegetative stage of ryegrass and on the third day of paddock occupation. Feeding behavior of hoggets is changed when supplementation is provided in different phenological stages of the grass and days of paddock occupation.